(untitled) (Radiasi : Jurnal Berkala Pendidikan Fisika, 2024)
Education in Indonesia has moved towards a broader digital approach. Information and communication technology development has encouraged many schools and educational institutions to look for new ways to integrate technology into teaching. One way is by utilizing a Learning Management System (LMS). One LMS platform that is quite widely used is Schoology. This research aims to find out how Schoology is used in physics learning in schools in Indonesia. The method used in this research is Systematic Literature Review (SLR), namely by finding, selecting, and synthesizing studies submitted for a specific question by following a systematic, transparent, and iterative process. Researchers chose 14 articles sourced from Google Scholar for analysis. These articles are grouped into certain groups to simplify the analysis process. This research found that the use of Schoology is quite good in facilitating physics learning in schools. However, Schoology should not be used in full, educators must play an active role so that students can still understand the material presented. Therefore, the learning method that is suitable for using Schoology in physics learning is the blended learning method. Keyword: LMS, Schoology, Physics Learning, Indonesian School